DAMPAK BROKEN HOME SEBAGAI IDE BERKARYA SENI ILUSTRASI - Gunadi; Murtafi, Fajriyah (Eduarts: Jurnal Pendidikan Seni, 2024)
The process of educating in a family involves positive support in the form of harmony and security. However, it can't be ignored that there are many problems faced by some families. Various problems in the family that sacrifice the growth and development of children can have a negative impact on children's conditions, especially psychological disorders that cause broken home situations. The choice of theme for this project is based on the author's personal experience, where as a child victim of a broken home, he also felt a sense of emptiness, sadness, disappointment and anxiety due to being a victim of parental separation. The author chose digital illustration to express his ideas because of the potential aspects of being able to be capable of this work style, the practicality of the work process, and the ease of accessing the results. The work process in this study project includes pre-production, production and post-production activities.